Insulin-like growth factor I stimulates lipid oxidation, reduces protein oxidation, and enhances insulin sensitivity in humans. - Hussain, M A (1993)
To elucidate the effects of insulin-like growth factor I (IGF-I) on fuel oxidation and insulin sensitivity, eight healthy subjects were treated with saline and recombinant human (IGF-I (10 micrograms/kg.h) during 5 d in a crossover, randomized fashion, while receiving an isocaloric diet (30 kcal/kg.d) throughout the study period. On the third and fourth treatment days, respectively, an L-arginine stimulation test and an intravenous glucose tolerance test were performed. A euglycemic, hyperinsulinemic clamp combined with indirect calorimetry and a glucose tracer infusion were performed on the fifth treatment day. IGF-I treatment led to reduced fasting and stimulated (glucose and/or L-arginine) insulin and growth hormone secretion. Basal and stimulated glucagon secretion remained unchanged. Intravenous glucose tolerance was unaltered despite reduced insulin secretion. Resting energy expenditure and lipid oxidation were both elevated, while protein oxidation was reduced, and glucose turnover rates were unaltered on the fifth treatment day with IGF-I as compared to the control period. Enhanced lipolysis was reflected by elevated circulating free fatty acids. Moreover, insulin-stimulated oxidative and nonoxidative glucose disposal (i.e., insulin sensitivity) were enhanced during IGF-I treatment. Thus, IGF-I treatment leads to marked changes in lipid and protein oxidation, whereas, at the dose used, carbohydrate metabolism remains unaltered in the face of reduced insulin levels and enhanced insulin sensitivity.